Genomic investigation into early onset protein-losing enteropathies: Therapeutic implications and insights into clusters of shared pathomechanisms - Sefer, Asena Pınar; Karakoç Aydıner, Elif; Urgancı, Nafiye; Kıykım, Ertuğrul; Baysoy, Gökhan; Fisher, Megan; Ertem, Deniz; Bayrak, Aykut; Varol, Fatma İlknur; İşlek, Ali; Çullu Çokuğraş, Fügen; Beşer, Ömer Faruk; et al. (Wiley, 2021)
[Abstract Not Available]
Keywords: Pathomechanisms; Therapeutic Implications; Enteropathies; Genomic Investigation